Associations between greenspace surrounding schools and lipid levels in Chinese children and teenagers. (15th January 2023) - Hu, Li-Xin; Fan, Shujun; Ma, Yinghua; Liu, Xiao-Xuan; Bao, Wen-Wen; Guo, Yuming; Hu, Li-Wen; Chen, Gongbo; Zeng, Xiao-Wen; Zou, Zhiyong; Yang, Bo-Yi; Ma, Jun; et al.
Abstract: Little evidence exists concerning the associations of greenspace with childhood lipid profiles and dyslipidemias, especially in developing countries and regions. We aimed to investigate the associations of greenspace surrounding schools with lipid levels and dyslipidemia prevalence among Chinese children and teenagers. We obtained baseline information and health data of 10, 408 children and teenagers (aged 6–18 years) who studied from 94 schools in China. We measured levels of four blood lipids: triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C). Dyslipidemias were defined using standard recommendations. Greenness surrounding schools were assessed using two satellite-based greenness indices, Normalized Difference Vegetation Index (NDVI) and Soil Adjusted Vegetation Index (SAVI) at 300-, 500-, and 1000-m circular buffers based on each school's latitude and longitude. We used random forest model combined with meteorological and remote sensing data to estimate air pollution levels surrounding each school. We used generalized linear mixed models to estimate the associations of greenness with lipid levels and dyslipidemias prevalence. We also performed sub-group and mediation analyses. An interquartile range (IQR) increase in NDVI500m was significantly associated with a 0.064 mmol/L (95% confidence interval [CI]: 0.083, −0.045) and 0.049 mmol/L (95% CI: 0.065, −0.033) decreased TC and LDL-C levels, respectively, as well as a 0.13-fold (95% CI: 0.01, 0.23) and 0.17-fold (95% CI: 0.01, 0.30) decreased odds of hypercholesterolemia and hyperbetalipoproteinemia, respectively. Associations were stronger in students aged ≤12 years and born to parents having lower education levels compared to their counterparts. Particle with aerodynamic diameter ≤2.5 μm (PM2.5 ) mediated 61.5% and 16.7% of the association of greenness with TG and LDL-C levels, respectively. In summary, higher school-based greenness exposure was beneficially associated with lipid levels among Chinese children and adolescents, and part of the association can be explained by lowed PM2.5 levels. Graphical abstract: Image 1 Highlights: Higher school-based greenspace exposure was associated with lower levels of blood lipids. Higher school-based greenspace exposure was associated with lower odds of types of dyslipidemia. PM2.5 mediated the association between school-based greenspace and blood lipids partially.